General e specific extenders nella legislazione sulla proprietà intellettuale in italiano, russo e tedesco - Chiara Marchesi; Francesco Caprioli (Linguistik Online)
This paper investigates the use of general and specific extenders in legislative texts on Intellectual Property Rights in Italian, Russian and German. The study aims to uncover their form, structure, and communicative functions within each of the three languages, with a particular focus on a contrastive perspective. While extenders have been predominantly analyzed in spoken discourse, this research demonstrates their significant role in written texts, in particular, in legislative language. Specifically, it argues that extenders serve as a deliberate strategy for introducing intentional vagueness, enabling legislators to craft provisions with varying degrees of specificity; by analyzing their internal modification, the study identifies extenders along a continuum of more or less indeterminacy. The analysis is based on a comparable multilingual corpus comprising three subcorpora, one for each language. Occurrences of general and specific extenders were identified in each of the three legislations, and their frequency, structural patterns, and degrees of modification were examined. The contrastive analysis reveals notable differences in frequency across the three languages, whilst highlighting similar structural trends, suggesting shared functional tendencies in legislative drafting.